Adherence to resistance training and hypocaloric diet among persons near retirement age - A secondary data analysis of three randomized controlled trials - Bauer, S; Reiter, L; Weijs, P J M; Schoufour, J D; Boirie, Y; Topinková, E; Memelink, R G; Verreijen, A M; Borenich, A; Eglseer, D (The journal of nutrition, health & aging, 2024)
OBJECTIVES: Adherence to lifestyle interventions is crucial for the treatment of obesity. However, there is little research about adherence to lifestyle interventions in persons around retirement age. The objectives of this study are (1) to identify factors associated with the adherence to resistance training and a hypocaloric diet and (2) to describe the association between adherence and changes in body composition outcome parameters. DESIGN: This secondary data analysis included three randomized controlled trials. SETTING & PARTICIPANTS: The inclusion criteria of the participants were an age of 55-75 years, a BMI ≥ 25 kg/m2 and receiving both a hypocaloric diet and resistance training. All participants were residing in the community. MEASUREMENTS: Adherence to hypocaloric diet was measured through the mean dietary intake on the basis of a 3-day dietary record. If the participant consumed at least 600 kcal less than the individual caloric requirements, they were considered adherent. Adherence to resistance training was achieved if ≥67% of the recommended training sessions were attended over the course of the study periods. RESULTS: 232 participants were included, 47.0% female, mean age 64.0 (±5.5) years. 80.2% adhered to resistance training and 51.3% adhered to a hypocaloric diet. Older age (Beta 0.41; 95% CI 0.05, 0.78; p = 0.028) and male sex (Beta 7.7; 95% CI 3.6, 11; p < 0.001) were associated with higher resistance training adherence. A higher BMI at baseline (Beta 6.4; 95% CI 3.6, 9.2; p < 0.001) and male sex (Beta 65; 95% CI 41, 88; p < 0.001) were associated with higher adherence to hypocaloric diet. CONCLUSION: We identified several associated factors (sex, age and BMI at baseline) that should be considered to promote adherence in future lifestyle intervention studies in persons around retirement age. We recommend including behavior change techniques in lifestyle interventions and consider sex-specific interventions to improve the adherence of women.
Keywords: Patient Compliance; kalorická restrikce; Male; Secondary Data Analysis; Obesity; odporový trénink; Diet, Reducing; důchod; sekundární analýza dat; randomizované kontrolované studie jako téma; obezita; Aged; Life Style; mužské pohlaví; senioři; redukční dieta; Resistance Training; adherence pacienta; Caloric Restriction; životní styl; lidé; ženské pohlaví; Humans; Body Mass Index; Retirement; Randomized Controlled Trials as Topic; složení těla; Body Composition; index tělesné hmotnosti; Female; lidé středního věku; Middle Aged